Molecular Identification and Characterization of Five Ganoderma Species from the Lower Volta River Basin of Ghana Based on Nuclear Ribosomal DNA (nrDNA) Sequences - Anang, A. K.; Gbewonyo, W. S. K.; Quarcoo, A.; et al (Journal of Fungi, 2024)
Ganoderma is a genus of biomedical fungus that is used in the development of numerous health products throughout the world. The Lower Volta River Basin of Ghana is an undulating land surface covered by extensive vegetation and water bodies and is rich in polypore mushrooms resembling various members of the Ganoderma genus. Despite the extensive biopharmaceutical benefits of Ganoderma spp., the isolates from the Lower Volta River Basin have not been properly characterized, thus limiting their use in the development of biotechnological products. In this study, Ganoderma spp. collected from the Lower Volta River Basin were genetically analyzed using the nuclear ribosomal sequences, the internal transcribed spacer 2 (ITS 2), the complete internal transcribed spacer (ITS), and the nuclear large subunit (nLSU). Blastn search and sequence analysis revealed that the sample we coded as Ganoderma LVRB-2 belongs to G. mbrekobenum, whereas Ganoderma LVRB-1, Ganoderma LVRB-14, and Ganoderma LVRB-16 belong to the species G. enigmaticum. Our analysis further demonstrates that Ganoderma LVRB-17 belongs to the species G. resinaceum. Thus, the five samples collected in the present study were positioned in three different distinct groups, namely G. mbrekobenum, G. enigmaticum, and G. resinaceum. The current data may serve as reference points for future studies.
Research Article
Keywords: Ganodermataceae; Lucidum; Reishi; molecular phylogenetic